Treatment of tuberculosis in a region with high drug resistance: outcomes, drug resistance amplification and re-infection. - Maryline Bonnet (Public Library of Science (PLoS), 2011)
Introduction Emerging antituberculosis drug resistance is a serious threat for tuberculosis (TB) control, especially in Eastern European countries. Methods We combined drug susceptibility results and molecular strain typing data with treatment outcome reports to assess the influence of drug resistance on TB treatment outcomes in a prospective cohort of patients from Abkhazia (Georgia). Patients received individualized treatment regimens based on drug susceptibility testing (DST) results. Definitions for antituberculosis drug resistance and treatment outcomes were in line with current WHO recommendations. First and second line DST, and molecular typing were performed in a supranational laboratory for Mycobacterium tuberculosis (MTB) strains from consecutive sputum smear-positive TB patients at baseline and during treatment. Results At baseline, MTB strains were fully drug-susceptible in 189/326 (58.0%) of patients. Resistance to at least H or R (PDR-TB) and multidrug-resistance (MDR-TB) were found in 69/326 (21.2%) and 68/326 (20.9%) of strains, respectively. Three MDR-TB strains were also extensively resistant (XDR-TB). During treatment, 3/189 (1.6%) fully susceptible patients at baseline were re-infected with a MDR-TB strain and 2/58 (3.4%) PDR-TB patients became MDR-TB due to resistance amplification. 5/47 (10.6%) MDR- patients became XDR-TB during treatment. Treatment success was observed in 161/189 (85.2%), 54/69 (78.3%) and 22/68 (32.3%) of patients with fully drug susceptible, PDR- and MDR-TB, respectively. Development of ofloxacin resistance was significantly associated with a negative treatment outcome. Conclusion In Abkhazia, a region with high prevalence of drug resistant TB, the use of individualized MDR-TB treatment regimens resulted in poor treatment outcomes and XDR-TB amplification. Nosocomial transmission of MDR-TB emphasizes the importance of infection control in hospitals.